Penggunaan Pendekatan Pembelajaran Berbasis HOTS Dalam Meningkatkan Kemampuan Problem Solving Di Sekolah Dasar - Raveldio Anelta (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
The focus of the article is to describe the use of a HOTS-based learning model that can improve the problem solving abilities of students in elementary schools as well as strategies that can be used in implementing HOTS learning in the classroom. This research uses a literature study method by examining several sources from journals and books related to the use of the HOTS-based learning model in improving the Problem Solving abilities of students in elementary schools. This research uses the Systematic Literature Review (SLR) method or literature review by systematically identifying journals. The steps in the SLR method are 1) Develop Research Questions, 2) Selection Criteria, 3) Developing The Search Strategy, 4) The Study Selection Process, 5) Appraising the Quality of Studies.